The Role Of Islamic Education In The Mental Health Of Generation Z: A Focus On Spirituality, Resilience, And Psychological Well-Being - Fera Ayu Lestariningtyas; Paradita Purnama; Siti Hotija; Benny Prasetiya (PT. Education Research Center, 2026)
This study discusses the role of Islamic education in supporting the mental health of Generation Z in the digital era. Generation Z faces various psychological pressures, such as anxiety, overthinking, academic pressure, cyberbullying, identity crises, and the influence of social media. This study uses a qualitative method with a literature review approach through an examination of various relevant scholarly sources. The findings show that Islamic education plays an important role in strengthening spirituality, building resilience, and improving students’ psychological well-being. Islamic values such as patience, gratitude, reliance on Allah, remembrance of Allah, prayer, self-reflection, and moral development can help Generation Z manage emotions, find meaning in life, and face pressure in a more positive way. In addition, Islamic education can also serve as an ethical guideline in the use of technology and social media. Thus, Islamic education functions not only as religious learning but also as a holistic approach to maintaining the mental health of Generation Z.